Bioethanol Production from Banana Peels using Different Pretreatments - Yousif, Yasir M.; Abdulhay, Hind S. (Asian Journal of Biological and Life Sciences, 2017)
Bioethanol is an attractive biofuel having a higher potential for energy security and environmental safety over fossil fuels. In this study, to obtain high concentration of ethanol from cellulosic materials, banana peels was pretreated with H2SO4 (0.5% v/v) and two types of ionic liquids (ILs) and cellulase enzyme. Fermentation process was conducted using Saccharomyces cerevisiae under anaerobic condition. All the pretreatment methods have been shown to effectively solubilize and hydrolyze cellulose and hemicellulose into monomeric sugars. It was proved that H2SO4gave the highest glucose concentration 34.2 g/L on the fourth day, while ethyl acetoacetate gave lower glucose concentration 27.3 g/L at fourth day. The concentration of the produced ethanol was measured every two days using ethanol sensor. The lowest mean concentration of ethanol produced from banana peels sample without pretreatment, H2SO4, ethyl acetoacetate, hexamethylphosphoramide and enzyme were 0.606, 3.936, 2.473, 6.286 and 2.553 g/L respectively, after 3 days fermentation. While the higher concentration of ethanol for the same samples (without pretreated and pretreated as above) were 8.143, 41.776, 24.853, 46.03 and 39.523 g/L respectively after 7 days of fermentation.
Keywords: Banana peels; Bioethanol; Enzyme Fermentation; Ionic liquid